Hak Berpikir, Hak Reproduksi, Dan Hak Kepemilikan Dalam Islam (Tinjauan Historis, Yuridis, dan Sosiologis) - Sokhi Huda (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2018)
Rights of thinking, reproduction rights, and property rights are part of the study of the values of civil society. First, historically, freedom of thought is inspired by the spirit of Islamic teachings, especially the first revelation, iqra'. The influence of iqra' is directly acquired by Muslims themselves, even contributing to the intellectual development of the world. Second, reproductive rights for women have a valid reference from the Qur'an, which must be protected and preserved for future generations. Respecting and safeguarding reproductive rights are the effort to preserve family, community, country, and religion. Thirdly, in Islamic law, property rights receive serious and detailed attention as does the taxonomy of the areas of Islamic law. In the taxonomy, the right of ownership obtains a juridical portion of all fields.